Metode dan Materi Pendidikan Islam dalam Hadis Jibril : (Pemahaman Hadis Melalui Pendekatan Filsafat Hermeneutika) - Agusri Fauzan; Ilham Syukri; Syahidin Syahidin (Rausyan Fikr: Jurnal Ilmu Studi Ushuluddin dan Filsafat, 2021)
As a process of knowledge transformation that will underlie the attitude of life of a Muslim, a qualified strategy is needed to teach the true teachings of Islam to the younger generation. The challenge for the current generation (millennial) is the opening of all channels of information that are very easy to obtain but not accompanied by good assistance from teachers and parents, so they are prone to absorb wrong information or even information that is not suitable for the size of the mind and soul. The next problem that occurs at this time is the reduced role of a teacher in shaping character and providing teaching materials that they should receive. This paper will invite to explore how the process of transformation of Islamic education was exemplified by the Prophet Muhammad and the Archangel Jibril before his companions regarding the methods used and what materials should be taught as the basis of Islamic knowledge. This research will use the literature method through the hadith literature and books that recite the hadith. The author also uses a philosophical and hermeneutic approach in understanding this hadith to get a new understanding but not out of an educational context. The research results from the understanding of this hadith are that a teacher plays a central role in the process of Islamic education so that teachers are expected to be able to appear as role models in front of their students, not display disgrace and personal ugliness, show friendly behavior to their students, have healthy scientific interactions, and teach basic things that are important in Islam according to the capacity of the soul and mind of the student.